Suzanne MacKenzie Memorial Lecture conceptually unclad: feminist geography and Aboriginal peoples * - Peters, Evelyn J. (The Canadian Geographer, 2004)
This paper argues that feminist geography can provide some useful lessons in an attempt to increase Aboriginal peoples' representation in geography. It asks the question: How can we use the example of feminist geography to think about a geography that is more inclusive of Aboriginal people? The paper focuses on the issues of content in teaching, drawing on examples from urban and social geography, and on methodological challenges, especially the issue of reflexivity. Feminist geographer Suzanne Mackenzie argued that an emerging feminist geography left the discipline ‘conceptually unclad’, challenging scholars to consider new theoretical frameworks and new perspectives. I argue that emphasising the geographies of Aboriginal people also enriches geography, including feminist geography.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; démographie; environnement; féminisme autochtone; géographie; géographie féministe; géographie urbaine; histoire et politique; méthodologie; pol4105; premier cycle; périodes historiques; sciences humaines; thématiques